Bukhara-India Relations during the Ashtarkhanid Dynasty - Jalolidinug’li, Davronov Mukhammad (Universitas Muhammadiyah Sidoarjo, 2022)
This article deals with the foreign diplomatic relations of the Ashtarkhanid dynasty with India, which ruled the Bukhara Khanate in the middle of the XVII-XVIII centuries. When the Ashtarkhanid dynasty came to power, it maintained active diplomatic relations with its closest neighbors in the region, the Khiva Khanate, Iran, the later Kokand Khanate, and other countries. In this regard, in the diplomatic relations with the Baburid dynasty we are talking about, the relations between the Baburid rulers Jahangir, Shah Jahan and subsequent rulers of Imamqulikhan, Nadir Muhammad and other Ashtarkhani rulers were discussed.